Promoting Chinese Students’ Creative Performance Through Collaborative Reasoning - Shufeng Ma (马淑风); Qiannan Zhou (周茜楠); Yaguang Li (李亚光); Senyu Chen (陈森宇) (ECNU Review of Education)
Purpose Creativity is highly valued by modern society; however, in China, there is a major challenge in creating school-based curricula or courses that promote students’ creativity. This study introduced an interactive learning format called Collaborative Reasoning (CR). The goal was to investigate whether CR would improve a student's ability to generate creative ideas. Design/Approach/Methods The data comprised 474 seventh graders from eight classes in a rural middle school in northern China. The eight classes were randomly assigned to two conditions: Four classes participated in CR discussions, and the remaining four classes were taught via teacher-directed Chinese reading classes. After participating in the CR discussions, students completed a Realistic Presented Problem test that was designed to evaluate their creative performance. Findings The results indicated that compared to the control students, CR students generated more effective solutions (fluency) and proposed a greater variety of solutions (flexibility) to three realistic problems. The solutions proposed by the CR students were more unique (novelty) and more useful in real-life situations (usefulness) than those proposed by the control group. Originality/Value Providing abundant opportunities for the exchange of ideas in a social context can boost students’ performance in creative problem-solving.